2019
DOI: 10.1097/aco.0000000000000720
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after paediatric anaesthesia

Abstract: PURPOSE OF REVIEW To review the developments within paediatric anaesthesia and describe the various factors that have contributed to the improvements in anaesthesia-related outcomes in children. RECENT FINDINGS During the years substantial improvements in paediatric anaesthesiarelated outcomes has derived from safety advances in equipment, drugs, human factor analysis, professional standardization and organization, subspecialty care and regionalization. However, universally agreed outcome measures are lacking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…One of the most comprehensive studies done, the APRICOT study, found a 1% reduction in critical respiratory events per year of experience of the anesthetizing provider and that centres with higher paediatric volumes have a lower rate of serious adverse events [24]. Experts now recommend that children with a higher risk as well as those under the age of 3 years should be managed by individuals and institutions with greater expertise and clinical volumes [25,37–39,41 ▪▪ ,42]. The data we have in the published literature are not truly representative of reality.…”
Section: Gaps and Challenges In Quality In Paediatric Anaesthesia Carementioning
confidence: 84%
See 1 more Smart Citation
“…One of the most comprehensive studies done, the APRICOT study, found a 1% reduction in critical respiratory events per year of experience of the anesthetizing provider and that centres with higher paediatric volumes have a lower rate of serious adverse events [24]. Experts now recommend that children with a higher risk as well as those under the age of 3 years should be managed by individuals and institutions with greater expertise and clinical volumes [25,37–39,41 ▪▪ ,42]. The data we have in the published literature are not truly representative of reality.…”
Section: Gaps and Challenges In Quality In Paediatric Anaesthesia Carementioning
confidence: 84%
“…Are there differences in outcomes based upon the experience, or lack thereof, of practitioners and centres caring for children? Although the evidence is not conclusive, several studies address the impact of experience and patient volume on outcomes, including the APRICOT study [20 ▪▪ ,25,34,35,36 ▪ ,37–40,41 ▪▪ ]. Nonpaediatric trained anaesthesiologists have higher rates of cardiac arrest versus paediatric anaesthesiologist [36 ▪ ], as well as an increased risk of bradycardia [34] and respiratory events [40].…”
Section: Gaps and Challenges In Quality In Paediatric Anaesthesia Carementioning
confidence: 99%
“…Systolic and mean blood pressures intervention thresholds are commonly accepted as low as to 25 mmHg and 17 mmHg (equal to 2 standard deviations below the mean preanesthetic values) in pediatric anesthesia. Whether these ‘hard’ limits, based on ambulatory [17] or preanesthetic [18,19] references, are safe for each patient is unknown [20–23]. In addition, the accuracy of blood pressure measurements can differ between 15 and 30% depending on the methods used especially below 30 mmHg [16 ▪ ,24], further increasing the uncertainty.…”
Section: Nectarine – the Lessonsmentioning
confidence: 99%